Prevalensi Kebiasaan Buruk Sebagai Etiologi Maloklusi Klas I Angle Pada Pasien Klinik Ortodonsia RSGM Universitas Jember Tahun 2015-2016 - Arimbi Gupitasari; Herniyati .; Leliana Sandra Devi Ade Putri (Pustaka Kesehatan, 2018)
Habit is a repetitive act that is done spontaneously and commonly occurs in childhood. A habit in the oral cavity that can cause malocclusion is called a bad habit. Bad habits can affect the dentofacial functions such as the process of chewing, talking, tooth occlusion, periodontal tissue, and esthetic. If bad habits continue after six years old, they can cause malocclusion. The etiology of malocclusions can be classified into general and local factors. Bad habit is one of the general factors that play a role in the occurrence of malocclusion. Kinds of bad habits are sucking the thumb/finger, pushing the tongue, biting the lips and nails, wrong swallowing habits, breathing through the mouth, and bruxism. The study investigate the prevalence of bad habit and bad habit that mostly happened as etiology of Angle’s Class I malocclusion in patient of Orthodontic Clinic RSGM Jember University. This descriptional study with total sampling technique was conducted by identifying dental records and study models of Angle’s Class I malocclusion that caused by bad habit. Obtained data were tabulated and analysed so that conclusion could be made. Prevalence of Angle’s Class I malocclusion caused by bad habits was 9.4% with the largest distribution in thumb/finger sucking (38,7%), in the age group 9-10 years (50%), and in the male gender (53,6%). Keywords: Prevalence of bad habits, etiology of Angle’s Class I malocclusion